Counseling and Education on the Prevention of Drug Abuse for Students of SMA Negeri 2 Sidrap - Eva Nirwana; Heriani; Erna Susilawati; Herwandi Sape; Muh. Ilham; Nudia Tuljannah (ITEKES Permata Ilmu Maros, 2025)
Socialization and education about the dangers of drug abuse among adolescents are essential to building a drug-free generation, considering that high school students play a critical role in shaping the nation’s future. Drug abuse not only causes health problems but also has long-term social, economic, and legal impacts. This community service activity was conducted at SMA N 2 Sidrap, involving 30 students aged 16–17 years. The purpose was to increase awareness and knowledge about the definition, classification, risks, and prevention of drug abuse. The program began with a pre-test, followed by an interactive lecture using PowerPoint slides and animated videos to make the material more engaging. Students were actively involved through discussions, case analysis, and a Q&A session. A post-test was administered to assess knowledge improvement. Results indicated a significant increase in understanding: definition (86.7% to 93.3%), classification (83.3% to 93.3%), impact (80% to 96.7%), and prevention (90% to 100%). The use of multimedia and interactive delivery proved effective in maintaining attention and promoting active learning. Beyond immediate knowledge gains, the activity fostered critical thinking and empowered students to act as peer educators, spreading anti-drug messages in their communities. This approach can serve as a sustainable model for other schools, contributing to broader efforts in reducing drug abuse prevalence among youth and supporting the creation of a healthy, resilient, and informed generation.